Groundwater science - Fitts, Charles R. [ (Charles Richard)] , 1953- (United Kingdom, 2013)
Covers groundwater's role in the hydrologic cycle and in water supply, contamination, and construction issues. This book is suitable for students and instructors in the geosciences (with focuses in hydrology, hydrogeology, and environmental science), and as a reference work for professional researchers